Kegiatan Pelatihan Implementasi Schoology dalam KBM untuk Meningkatkan Keahlian dan Etika Siswa SMA Menggunakan ICT - Anita Anggraeni; Cynantia Rachmijati (LPPM UNINUS, 2021)
The quality of learning in general at SMK PGRI 2 Cimahi based on the results of discussions with the English teacher is that in general they have enough enthusiasm to learn English, but learning is still fixated on learning resource media in the form of worksheets. Thus they are more focused on the results of working on worksheets. The development of information and communication technology has brought enormous changes to the advancement of the world of education. The form of the development of information technology applied in the world of education is E-Learning. One of the platforms that can be used as an interactive learning medium is Schoology. The use of Schoology media requires students to always be connected to the internet network. Positive supervision from teachers and parents is expected so that students do not access things that are negative in nature. Therefore, the community service activity entitled